W and Z boson production in p p̄ collisions at √s = 1.8 TeV - Abachi, S; Abbott, B; Abolins, M; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alitti, J; Álvarez, G; Alves, G; et al. (1995)
The inclusive cross sections times leptonic branching ratios for W and Z boson production in p p̄ collisions at √s = 1.8 TeV were measured using the D0 detector at the Fermilab Tevatron collider: σWB(W → e ν) = 2.36 ± 0.07 ± 0.13 n b, σWB(W → μν) = 2.09 ± 0.23 ± 0.11 n b, σZB(Z → e+e-) = 0.218 ± 0.011 ± 0.012 n b, and σZB(Z → μ+μ-) = 0.178 ± 0.030 ± 0.009 n b. The first error is the combined statistical and systematic uncertainty, and the second reflects the uncertainty in the luminosity. For the combined electron and muon analyses we find σWB(W → lν)/σZB(Z → l+l-) = 10.90 ± 0.49. Assuming standard model couplings, this result is used to determine the width of the W boson, Γ(W) = 2.044 ± 0.093 GeV.